Pola Penanganan Pemukiman Kumuh Kelurahan Abeli Kota Kendari - Heber, Heber; Kadir, Abdul; Kadir, Ishak (Jurnal Manajemen Rekayasa (Journal of Engineering Management), 2022)
Slum settlements are uninhabitable settlements because of building irregularities, high levels of building density, and the quality of buildings and facilities and infrastructure that do not meet the requirements, while slum housing is housing that has decreased quality as a residential and slum area is an area with high population density in a city.The purpose of the study was to describe the Pattern of Handling Quality Improvement of Slum Settlements from the Aspects of Environmental Physical Management in Abeli Village.The research method is descriptive research by describing the phenomenon and method of analysis using the Triagulation method.The results of the study show that the scenario of slum handling in Abeli Village is done by using technical patterns of handling slum patterns; (1) Restoration and (2) Rejuvenation, through technical handling with physical handling on; (1) house building; (2) environmental roads; (3) provision of drinking water; (4) environmental drainage; (5) waste water management; (6) waste management; (7) providing fire protection and (8) providing green open space.To complete the slum handling in a coordinated manner, the collaboration model is carried out, with the effectiveness of (1) Participation; (2) Acceptance; (3) Communication; (4) Mutual trust; and (5) Sharing.In optimizing slum handling, it is expected that joint arrangements in the form of a participatory agreement, because in handling, with collaborative models that are in accordance with the agreement with the community.